EVALUASI PENATAUSAHAAN ASET TETAP PADA KANTOR DINAS OLAHRAGA DAN PEMUDA PROVINSI PAPUA - Adonia Abigael Aibekob; Syaikhul Falah; Arius Kambu (Universitas Cenderawasih, 2021)
This study aims to obtain a clear picture of the effects of recording, inventorying and reporting on the administration of fixed assets at the Papua Province Sports and Youth Office. The type of data used is qualitative data and quantitative data. Primary and secondary data is the data source used. Data collection techniques are used, namely field data and library data studies. The study was conducted using quantitative descriptive data analysis techniques consisting of research instrument test, classic assumption test, and multiple regression analysis. The results of the study show that recording, inventorying and reporting partially has a positive and significant effect on the administration of fixed assets at the Papua Province Sports and Youth Office. Recording, Inventory and Reporting simultaneously have a positive and significant effect on the administration of fixed assets at the Papua Province Sports and Youth Office. Recording is the dominant factor that has a significant effect on the administration of fixed assets at the Papua Province Sports and Youth Office